Urgent manifestations of immunoglobulin G4-related disease. (2nd January 2021) - Della-Torre, E; Mancuso, G; Lanzillotta, M; Ramirez, GA; Arcidiacono, PG; Capurso, G; Falconi, M; Dagna, L
Abstract : Objective : Immunoglobulin G4 -related disease (IgG4 -RD) is considered a chronic condition with insidious presentation, but clinical experience suggests that disease onset prompts admission to the emergency department (ED) in a sizeable proportion of patients. We assessed the prevalence of acute manifestations associated with IgG4 -RD onset requiring referral to the ED. Method : We revised our database and identified patients admitted to the ED because of symptoms latterly attributed to IgG4 -RD onset (Group 1) and those who were referred to our outpatient clinic without previous urgent manifestations (Group 2). Acute manifestations were clustered based on the anatomical region affected by IgG4 -RD. Epidemiological, clinical, and serological features of Groups 1 and 2 were compared. Results : The study included 141 patients with IgG4 -RD. Of these, 76 (54%) presented to the ED at disease onset. The most common clinical manifestations requiring admission to the ED were jaundice (53%), abdominal pain (41%), and fever (10%). Gastrointestinal involvement was the most frequent cause of referral to the ED (71% of cases), followed by involvement of the retroperitoneum (14.5%) and the nervous system (6.6%). Pancreatobiliary involvement was significantly more frequent in Group 1 than in Group 2. Head and neck, and salivary and lacrimal gland involvement was more frequent in Group 2 than in Group 1. The diagnostic delay was significantly shorter in Group 1 than in Group 2. Conclusion : Clinical manifestations associated with IgG4 -RD onset require referral to the ED in most cases. This finding contrasts with the general view of IgG4 -RD as a condition with non-acute presentation.